Evaluating Quality of Chatbots and Intelligent Conversational Agents of BCA (VIRA) Line - Mudofi, Luthfi Nurul Hidayah; Yuspin, Wardah (International Journal Labs, 2022)
Background: The use of technology in the financial sector greatly supports its productivity. Including the use of Artificial Intelligence or Artificial Intelligence that makes activities in the financial sector faster and more efficient. PT. Bank Central Asia also implemented Artificial Intelligence technology by launching a chatbot feature called VIRA. Although this vira provides various conveniences this feature has a disadvantage of this feature is that the account can be accessed without using a pin, but only with a card number and OTP code. Aim: This research aims to look at the legal protection of the use of VIRA chatbots in BCA customers' banking activities. Method: This research is included in the type of empirical juridical legal research with library research and vira application observation. Findings: The results showed that BCA customers can only access personal data using VIRA. The main facilities of chatbot VIRA are more general information services and promotions for customers. In addition, the account is not automatically logged out, so when the phone is lost others may be able to access the account of the mobile phone owner through VIRA.